Youth employment: scene to the bicentennial - Moscoso Paucarchuco, Ketty Marilú (2021)
This study is of a descriptive exploratory nature, with a qualitative approach, based on a documentary review, of a narrative type and has the objective of analyzing the situation of youth employment in Peru, within the framework of the celebrations of the bicentennial for independence. Unemployment has hit the Peruvian population hard, more so on young people and even more so on young women. Although it is true that the rates of its decline show slight favoring, these data will be modified by the recent pandemic situation that is happening. The intervention of the State with policies for the protection and promotion of young people in the search for their first job is important, giving them solidity through the formation of hard and soft skills, which facilitate competitive performance in their work. The private company plays a basic role and is reflected in its corporate social responsibility; providing the facilities, incentives and motivations to these, is the concern of the future political leaders of our country.